Implementasi Pembelajaran Bahasa Arab Berbasis Digital pada Kurikulum Berbasis Kompetensi di Madrasah Tsanawiyah - Mardhotillah, Azzah Diana; Syarifah, Ainun (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
Era Industri 4.0 demands digital literacy and 21st-century competencies in education, including Arabic language learning under Competency-Based Curriculum (KBK) in Indonesian madrasahs. Preliminary observations at MTsN 1 Lamongan revealed discrepancies between KBK's emphasis on communicative maharah lughawiyah (listening, speaking, reading, writing) and classroom realities, marked by limited digital infrastructure and suboptimal interactive media used teacher capacity in order to fully achieve the goals of the competency-based curriculum. This qualitative descriptive study aimed to: (1) describe KBK implementation in Arabic learning within Industry 4.0 contexts, (2) identify barriers related to facilities, digital literacy, and performance assessment, and (3) analyze teachers' strategies for optimization. Data were collected through classroom observations, teacher-student interviews, and documentation from Grade 7 Arabic classes, analyzed thematically. Findings indicate teachers integrate digital media (projectors, smartboards, smartphones) with blended low-tech approaches and collaborative activities (group discussions, chain dialogues). However, implementation faces constraints including uneven LCD/internet access, students' low digital literacy, device distractions, and unstructured assessment rubrics. Teachers mitigate these through vocabulary scaffolding, device scheduling, flexible classroom management, and sustained motivation, positioning facilitation as pivotal to KBK success despite infrastructural limitations. Recommendations include infrastructure enhancement, digital literacy training, and authentic rubric development to optimize KBK implementation.